2017
DOI: 10.1007/s00167-017-4595-6
|View full text |Cite
|
Sign up to set email alerts
|

Excellent healing rates and patient satisfaction after arthroscopic repair of medium to large rotator cuff tears with a single-row technique augmented with bone marrow vents

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…Other studies have described results using the single-row fashion in cuff repair. 9,24,27 Snyder and Burns 31 indicated that the uncovered bone marrow droplets would flow from the vents and form the crimson duvet, covering the repaired rotator cuff. However, Yoon et al 37 proposed that the uncovered footprint may not maintain bone marrow droplets, which would subsequently vanish into the subacromial space.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have described results using the single-row fashion in cuff repair. 9,24,27 Snyder and Burns 31 indicated that the uncovered bone marrow droplets would flow from the vents and form the crimson duvet, covering the repaired rotator cuff. However, Yoon et al 37 proposed that the uncovered footprint may not maintain bone marrow droplets, which would subsequently vanish into the subacromial space.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike conventional SR, Dierckman et al and Dini and Snyder reported that arthroscopic rotator cuff repair using a single-row technique (also referred to as “Southern California Orthopedic Institute [SCOI] row”) consisting of medially-based, triple-loaded anchors augmented with bone marrow vents in the rotator cuff footprint lateral to the repair results in > 90% healing rates and excellent patient reported clinical outcomes [ 14 , 15 ]. They proposed that a single row with three sutures per anchor yields the strongest possible repair with the least possible tension on the construct; however, verification of such an advantage based on biomechanical studies is limited.…”
Section: Introductionmentioning
confidence: 99%
“…27,29,32,36,41 Bone marrow vents have shown promise in improving the bone-tissue interface healing of many soft tissue injuries by allowing autologous marrow-derived cells to reach the repair site. 9,37 Bone marrow venting is a comparatively expeditious surgical procedure, has no issue of cellular incompatibility, and may be accomplished through vented tissue anchors or through separate bone puncture holes. 9,46 Potential problems with bone puncture holes for bone marrow venting is that it can weaken the bone around the venting holes, possibly leading to inadequate anchor fixation in the bone.…”
mentioning
confidence: 99%
“…9,37 Bone marrow venting is a comparatively expeditious surgical procedure, has no issue of cellular incompatibility, and may be accomplished through vented tissue anchors or through separate bone puncture holes. 9,46 Potential problems with bone puncture holes for bone marrow venting is that it can weaken the bone around the venting holes, possibly leading to inadequate anchor fixation in the bone. 37 Scaffolds or ''patches'' have also shown value for augmenting torn tissue and promoting tissue thickening.…”
mentioning
confidence: 99%